Novel mechanisms for the vitamin D receptor (VDR) in the skin and in skin cancer. Issue 148 (April 2015) - Bikle, Daniel D.; Oda, Yuko; Tu, Chia-Ling; Jiang, Yan
Highlights: The VDR plays a key role in epidermal proliferation, differentiation, and hair follicle cycling. Calcium via the calcium sensing receptor (CaSR) is central to these actions of VDR. VDR utilizes coregulators such as Med 1, SRC3, and hairless for its different actions. The ligand 1, 25(OH)2 D is not required for all actions of the VDR. Mice lacking VDR and CaSR develop skin tumors spontaneously. Abstract: The VDR acting with or without its principal ligand 1, 25(OH)2 D regulates two central processes in the skin, interfollicular epidermal (IFE) differentiation and hair follicle cycling (HFC). Calcium is an important co-regulator with 1, 25(OH)2 D at least of epidermal differentiation. Knockout of the calcium sensing receptor (CaSR) in addition to VDR accelerates the development of skin cancer in mice on a low calcium diet. Coactivators such as mediator 1 (aka DRIP205) and steroid receptor coactivator 3 (SRC3) regulate VDR function at different stages of the differentiation process, with Med 1 essential for hair follicle differentiation and early stages of epidermal differentiation and proliferation and SRC3 essential for the latter stages of differentiation including formation of the permeability barrier and innate immunity. The corepressor of VDR, hairless (HR), is essential for hair follicle cycling, although its effect on epidermal differentiation in vivo is minimal. In its regulation of HFC and IFE VDR controls two pathways—wnt/β-catenin and sonic hedgehog (SHH). In the absence of VDR these pathways are overexpressed leading to tumor formation. Whereas, VDR binding to β-catenin may block its activation of TCF/LEF1 sites, β-catenin binding to VDR may enhance its activation of VDREs. 1, 25(OH)2 D promotes but may not be required for these interactions. Suppression of SHH expression by VDR, on the other hand, requires 1, 25(OH)2 D. The major point of emphasis is that the role of VDR in the skin involves a number of novel mechanisms, both 1, 25(OH)2 D dependent and independent, that when disrupted interfere with IFE differentiation and HFC, predisposing to cancer formation. This article is part of a Special Issue entitled '17th Vitamin D Workshop'.